The effect of N-acetylcysteine in a combined antibiofilm treatment against antibiotic-resistant Staphylococcus aureus. (3rd May 2020) - Manoharan, Arthika; Das, Theerthankar; Whiteley, Gregory S; Glasbey, Trevor; Kriel, Frederik H; Manos, Jim
Abstract: Background: The WHO declared Staphylococcus aureus as a 'pathogen of high importance' in 2017. One-fifth of all bloodstream-related infections in Australia and 12 000 cases of bacteraemia in the UK (2017–18) were caused by the MRSA variant. To address the need for novel therapies, we investigated several permutations of an innovative combination therapy containing N -acetylcysteine (NAC), an antibiotic and an enzyme of choice in eradicating MRSA and MSSA biofilms. Methods: Biofilm viability (resazurin assay) and colony count methods were used to investigate the effect of NAC, antibiotics and enzymes on S. aureus biofilm disruption and killing. The effects of NAC and enzymes on the polysaccharide content of biofilm matrices were analysed using the phenol/sulphuric acid method and the effect of NAC on DNA cleavage was determined using the Qubit fluorometer technique. Changes in biofilm architecture when subjected to NAC and enzymes were visualized using confocal laser scanning microscopy (CLSM). Results: NAC alone displayed bacteriostatic effects when tested on planktonic bacterial growth. Combination treatments containing 30 mM NAC resulted in ≥90% disruption of biofilms across all MRSA and MSSA strains with a 2–3 log10 decrease in cfu/mL in treated biofilms. CLSM showed that NAC treatment drastically disrupted S. aureus biofilm architecture. There was also reduced polysaccharide production in MRSA biofilms in the presence of NAC. Conclusions: Our results indicate that inclusion of NAC in a combination treatment is a promising strategy for S. aureus biofilm eradication. The intrinsic acidity of NAC was identified as key to maximum biofilm disruption and degradation of matrix components.